Factors Related to the Incident of Dyspepsia Syndrome - Rahayu, Sri; ., Sihombing; Eko Pertiwi, Wiwik (KnE Social Sciences, 2023)
Dyspepsia syndrome is heartburn, nausea, early satiety, vomiting, belching, a full stomach, and bloating. Factors that influence dyspepsia syndrome are age, gender, occupation, eating pattern, and stress levels. The study aims to determine the factors associated with the incidence of dyspepsia syndrome in the inpatient ward of Kencana Hospital Serang City in 2021. This study used a cross-sectional study design, and the data were analyzed bivariate with a Chi-square test approach. The study population were all patients in the internal medicine inpatient room as many as 57 people. The sample in this study is total sampling. Variables of age, gender, occupation, eating pattern were collected with questionnaire, stress levels used DASS questionnaire. The results showed that the variables of age (pv = 0.018), gender (pv = 0.035), occupation (pv = 0.008), and eating pattern (pv = 0.024) had a significant relationship with the incidence of dyspepsia syndrome, while the stress level variable had no relationship with the incidence of dyspepsia syndrome. It is expected to improve health services by providing health education to respondents who suffer from dyspepsia so that they can add information about dyspepsia for them. Keywords: dyspepsia syndrome, eating pattern, stress level